2019
DOI: 10.3390/ijerph16020293
|View full text |Cite
|
Sign up to set email alerts
|

Restorative Effects of Classroom Soundscapes on Children’s Cognitive Performance

Abstract: Previous studies have examined the restorative benefits of soundscapes on adults’ cognitive performance, but it was unclear whether those benefits would be possible for children. In this paper, two experiments applied a before–after design to explore the restorative effects of different soundscapes on children’s sustained attention and short-term memory, respectively, in a simulated classroom situation. In Experiment 1, 46 children aged 8–12 were first mentally fatigued by performing an oral arithmetic task an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
(60 reference statements)
0
21
1
Order By: Relevance
“…Higher NO2 exposure was related to an increased likelihood to report high noise annoyance, but the impact depended on traffic noise level, thus suggesting an interaction effect. In detail, the effect of NO2 resulted stronger in people exposed to low levels of noise (DNL ≤ 45 dBA) than in people exposed to medium noise levels (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). As a result, the authors suggest that a multiplier reduction in noise annoyance can be achieved through a simultaneous reduction of NO2 levels and noise levels [35].…”
Section: Factors Influencing the Acoustic Perception Of Indoor Residementioning
confidence: 99%
See 1 more Smart Citation
“…Higher NO2 exposure was related to an increased likelihood to report high noise annoyance, but the impact depended on traffic noise level, thus suggesting an interaction effect. In detail, the effect of NO2 resulted stronger in people exposed to low levels of noise (DNL ≤ 45 dBA) than in people exposed to medium noise levels (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). As a result, the authors suggest that a multiplier reduction in noise annoyance can be achieved through a simultaneous reduction of NO2 levels and noise levels [35].…”
Section: Factors Influencing the Acoustic Perception Of Indoor Residementioning
confidence: 99%
“…This suggests that reducing noise annoyance would allow for higher noise levels both outdoor and consequently indoor, without harmful effects on other health outcomes. Furthermore, the creation of acoustic environments positively perceived by people has the potential not only to reduce health risks but also to induce positive-related health effects [10,59,60].…”
Section: Factors Influencing the Acoustic Perception In Indoor Residementioning
confidence: 99%
“…By going beyond noise annoyance reduction and sound level minimization, a broader picture could be captured on perceptual and health outcomes resulting from the experience of the acoustic environment. Accordingly, the literature has reported that, in addition to health risks reduction, even positive-related health effects may result from acoustic environments being positively perceived by people [47,64,120]. Understanding the potential of a positive acoustic experience to enhance building users´health and well-being requires a perceptual, soundscape perspective to be adopted in order to comprehend what makes an acoustic environment sound "positive".…”
Section: Rethinking Nv For Positive Acoustic Alliesthesia Under the Imentioning
confidence: 99%
“…Di Blasio and colleagues [20] focus on the overall comfort and performance of open-plan office workers when affected by undue noise coming from irrelevant speech. Similarly, looking at cognitive performance, Shu and Ma [21] carry out a study to explore the restorative effects of different soundscapes on children's sustained attention and short-term memory.…”
Section: Supportive Indoor Soundscapes-a Perceptual Perspective On Bumentioning
confidence: 99%